Distres Psikologis pada Remaja yang Mengalami Kedukaan Akibat COVID-19 (Sebuah Telaah Literatur Sistematik) - Citraningrum, Donna Ayu; Surjaningrum, Endang R (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
COVID-19 that has happened up until now brings the deaths of millions of people. The experience of losing the loved one and suffering different situations than usual with many rules regarding funerals causes grief which results in psychological distress for the grieving individuals. Moreover, when grief is experienced by adolescents. This research aimed to systematically observe the psychological distress experienced by adolescents as a result of grief related to the loss of the beloved one due to COVID-19. The journals applied for the literature review in this research were taken from three journal databases: proquest, sciencedirect and SAGE, published in 2020-2021. As result, 171 eligible articles were extracted and synthesized according to review objectives. The result showed that there was psychological distress in adolescents who experienced grief such as hopelessness as well as anxiety, and most of them showed indications leading to worse mental disorders such as depression, panic attacks, paranoia, and suicide.